PENGARUH GAYA KEPEMIMPINAN TERHADAP KOMITMENORGANISASI KARYAWAN UKM DI WILAYAH DEPOK JAWA BARAT - Suryanto, Dede; Prihatiningsih, Wulan (UI Scholars Hub, 2016)
Organizational commitment is a psychological state that characterizes employee relationship with the organization. It has implication for the decision to continue membership in the organization. Employee with high commitment is a valuable asset in operating the company in order to maintain Company’s sustainability. This research proposes that organizational commitment is influenced by leadership style. The hypothesis is tested using data obtained from 60 respondents who work in Small and Medium enterprises in Depok. The results shows that transformational leadership style affects positively on affective commitment but it doesn’t affect normative commitment. Besides that, transactional leadership style doesn’t affect continuance commitment, while passive / avoidant leadership style does not affect affective commitment.